Digital Data Protection Laws : A Review - Sreevalli Seetharamu; Lakshmi Manasa CN; Anisha Bhattacharya; Dr. Chitra BT (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Over the past couple of years, India has noted the significance of digital data and its protection. This article talks about the arising and present regime of India’s laws on digital data protection, specifically diving into the Digital Personal Data Protection Act, 2023. This act has tried to balance the scales between individual privacy rights and the economic growth that needs to be brought about by data-driven economic progress. A comparative study regarding data protection laws in the UK and US have been established, and this has been compared with DPDP 2023 in order to provide suggestions for improvements for the act. This paper examines various provisions, objects, and shortcomings of the DPDP Act, bringing into sharper focus areas of concern, notably government exemptions, data localization, and inadequacies in regard to a strong data protection authority. The article concludes with comparative analysis to shed light on strengthening the data protection regime in India and also makes some recommendations for future legislation in the light of emerging technologies like AI.